PEMBERDAYAAN MASYARAKAT DESA BOCEK MELALUI PELATIHAN DIVERSIFIKASI PRODUK OLAHAN IKAN LELE MENJADI DIMSUM INOVATIF - Heder Djamaludin; Desy Arisandi; Eddy Suprayitno; Hardoko Hardoko; Yahya Yahya; Muhamad Firdaus; Hartati Kartikaningsih; Anies Chamidah; Muhammad Luthfi Denendra; Andreas Rafael; Yunita Eka Puspitasari (Jurnal Abdi Insani, 2026)
Bocek Village, located in Karangploso District, Malang Regency, has considerable potential in freshwater fisheries, particularly in catfish (Clarias sp.) cultivation. However, most of the harvested fish are still sold in fresh form without any processing, resulting in low economic value. The lack of knowledge and skills among the community in processing fish into value-added products remains a major constraint. Therefore, training activities are needed to enhance the community’s capacity in developing innovative catfish-based food products utilizing local resources. This activity aimed to improve the knowledge, skills, and motivation of the Bocek Village community, particularly members of the Family Welfare Empowerment (PKK) group, in processing catfish into innovative dimsum products that are economically valuable and consumer-preferred. The training applied the Participatory Action Learning System (PALS) approach, which included pre-test, theoretical instruction, hands-on practice in producing innovative catfish dimsums, hedonic testing, and post-test evaluation. The hedonic test involved 34 untrained panelists who assessed the appearance, aroma, taste, and texture attributes of the product. The results showed an increase in participants’ understanding, with the average score rising from 56.8% on the pre-test to 87.3% on the post-test. The innovative catfish dimsum received high acceptance, with mean scores of 6.2 for appearance, 5.9 for aroma, 6.5 for taste, and 6.3 for texture. Participants also demonstrated good application of sanitation principles and local ingredient innovation. This program effectively enhanced fish processing skills and has the potential to support economic independence in Bocek Village through the development of local superior products based on catfish.